2017
DOI: 10.1590/198053144297
|View full text |Cite
|
Sign up to set email alerts
|

Diferencial educacional entre beneficiários e não beneficiários do Programa Bolsa Família

Abstract: ABSTRACT

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
2
0
2
Order By: Relevance
“…23 Publications addressing the program's impact have shown that it reduced poverty and hunger, child mortality and improved access to elementary education. 24 , 25 , 26 Auxilío Financeiro Emergencial , was an emergency financial assistance program implemented during the COVID-19 pandemic (Apr 2020 through Oct 2021) targeting low-income informal workers, the self-employed, and those already registered in Bolsa Familia (who are eligible to receive this transfer in place of their regular Bolsa Familia transfer). 27 Compared to Bolsa Familia, Auxilío Financeiro Emergencial eligibility criteria was broader and in 2020, 294 billion BRL were transferred to approximately 67 million beneficiaries (72% of them were not previously beneficiaries of the Bolsa Familia program).…”
Section: Methodsmentioning
confidence: 99%
“…23 Publications addressing the program's impact have shown that it reduced poverty and hunger, child mortality and improved access to elementary education. 24 , 25 , 26 Auxilío Financeiro Emergencial , was an emergency financial assistance program implemented during the COVID-19 pandemic (Apr 2020 through Oct 2021) targeting low-income informal workers, the self-employed, and those already registered in Bolsa Familia (who are eligible to receive this transfer in place of their regular Bolsa Familia transfer). 27 Compared to Bolsa Familia, Auxilío Financeiro Emergencial eligibility criteria was broader and in 2020, 294 billion BRL were transferred to approximately 67 million beneficiaries (72% of them were not previously beneficiaries of the Bolsa Familia program).…”
Section: Methodsmentioning
confidence: 99%
“…As condições das pessoas mais vulneráveis ressaltam a necessidade de políticas sociais, como o Programa Bolsa Família. Este programa é uma ampliação das políticas de distribuição de renda do país para a população com menor poder aquisitivo, criado em 2004 para garantir acesso aos serviços essenciais como alimentação, saúde e educação (Gonçalves, Menicucci, & Amaral, 2017).…”
Section: Ações Governamentais Para Mitigar a Desigualdade Socialunclassified
“…The conditions of the most vulnerable people underscore the need for social policies such as the Bolsa Família Program. This program is an expansion of the country's income distribution policies for the population with lower purchasing power, created in 2004 to guarantee access to essential services such as food, health, and education (Gonçalves, Menicucci, & Amaral, 2017).…”
Section: Government Actions To Mitigate Social Inequalitymentioning
confidence: 99%